Hemobilia - Navuluri, Rakesh (Seminars in Interventional Radiology, 2016)
Hemobilia is a rare source of upper gastrointestinal bleeding, though the incidence is increasing along with the rise in minimally invasive biliary interventions. Prompt diagnosis and treatment rests on having appropriate clinical suspicion which should be based on the patient's presenting signs and symptoms, as well as history including recent instrumentation. Endoscopy should be reserved for cases of upper gastrointestinal bleeding with low suspicion for hemobilia. Interventional radiology may be the first-line diagnostic and therapeutic option for patients with a high suspicion of hemobilia. While embolization is the mainstay of therapy, other options include thrombin injection, stent placement, and/or placement of a percutaneous biliary drain. Surgery should be reserved for failed treatment by interventional radiology.
Keywords: hemobilia; imaging; interventional radiology; embolization